2008
DOI: 10.1370/afm.761
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Pedometer-Based Walking Interventions and Weight Loss

Abstract: PURPOSE Cross-sectional studies show that individuals who walk more tend to be thinner than those who walk less. This does not mean, however, that the association between higher step counts and lower weight is causal or that encouraging sedentary individuals to increase step counts helps them lose weight. METHODSIn this meta-analysis, we searched 6 electronic databases and contacted pedometer experts to identify pedometer-based walking studies without a dietary intervention that reported weight change as an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
239
5
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(283 citation statements)
references
References 38 publications
14
239
5
15
Order By: Relevance
“…A meta-analysis of 25 years of lifestyle weight loss programs specifically showed that aerobic exercise alone (mean, 15.6 weeks) decreased BMI by 0.8 and initial weight by 3.6% on average (41). In a meta-analysis of nine pedometer-based interventions, there was a strong dose-response relation whereby longer intervention duration was associated with greater weight loss (44). Another review of eight recent (2000-2006) exercise randomized control trials (RCT) suggested that longer duration of physical activity is optimal for decreasing body weight and adiposity (45).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of 25 years of lifestyle weight loss programs specifically showed that aerobic exercise alone (mean, 15.6 weeks) decreased BMI by 0.8 and initial weight by 3.6% on average (41). In a meta-analysis of nine pedometer-based interventions, there was a strong dose-response relation whereby longer intervention duration was associated with greater weight loss (44). Another review of eight recent (2000-2006) exercise randomized control trials (RCT) suggested that longer duration of physical activity is optimal for decreasing body weight and adiposity (45).…”
Section: Resultsmentioning
confidence: 99%
“…We chose to exclude pedometers, as they have previously been reviewed and demonstrated modest weight loss. 48,49 We only considered trials conducted after the year 2000, as few PC-based studies were published before that date and any prior technologyassisted interventions would likely be obsolete. 50 …”
Section: Eligibility Criteriamentioning
confidence: 99%
“…29 A meta-analysis of pedometer-based walking programmes reported modest weight loss of 0.05 kg per week, with longer programmes leading to greater weight loss than shorter ones. 30 Wider objectives of management of overweight and obesity such as optimising lipids, glycaemic control, and blood pressure, may be achieved by modest weight loss of 5-10%, improved nutrition, and modest increases in physical activity. 31 Two recent reviews of randomised controlled trials in patients with hypertension or pre-diabetes reported such benefits from modest weight loss.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%